Exploring the impacts of early sport specialization among Québec`s adolescent hockey players - Huard Pelletier, V.; Lemoyne, J. (Journal of Expertise, 2020)
Early sport specialization has recently become a growing concern among sport federations, because it is associated with deleterious effects that may lead to sport attrition. More specifically in ice hockey, some studies found that the dropout rate is approximately 5% per year. This study aims to assess the prevalence of early sport specialization (ESS) among adolescent hockey players and analyze the relationship between the degree of ESS and characteristics associated with long-term sports participation such as attitudes toward other active behaviors, physical self-perceptions, and social support. A sample of 404 adolescent hockey players (competitive/elite vs. recreational) from the province of Québec (Canada) completed a questionnaire during their hockey season. Group comparisons were performed based on ESS degree and for both levelsof competition.Results revealed that early sport specialization seemed to be more prevalent among less competitive, non-elite, and older players. Furthermore, players who reported ESS showed less favorable scores on self-reported physical activity, less favorable attitudes toward sport and exercise, less social support in their sport, and they had lower scores in physical self-perceptions. This study highlights the importance of introducing adolescents to a range of sports and other types ofactive behaviors, especially during the off-season. Practical implications for sport stakeholders who want to promote long-term athlete development are discussed.